Metode Qiroati dalam Pembelajaran Al-Qur’an: Studi Kasus di SDIT Insantama Leuwiliang - Eneng Farida; Hana Lestari; Zulfikar Ismail (LPPM Institut Nasional Laa Roiba Bogor, 2021)
The Qiroati method is a method for studying and understanding the Koran. The purpose of this study was to analyze the application of the Qiroati method in learning Al-Quran at SDIT Insantama Leuwiliang. The research method is a case study. The research was conducted at SDIT Insantama Leuwiliang with 30 respondents as the subject of research. The data collection techniques used were interviews, observation and documentation. The data validity used time and place triangulation. The data analysis technique uses interactive analysis with data reduction steps, data presentation, and drawing conclusions. The results of this study are in the form of information about the Qiroati method applied at SDIT Insantama Leuwiliang. The results obtained are that the Qiroati method applies a system and how to read fluently, quickly, precisely, correctly and tartly without having to spell it. The teaching model in the Qiroati method uses teaching aids for classical teaching containing material in the Qiroati volume book. The teaching model in the Qiroati method uses teaching aids for classical teaching which contain material on the pages of the Qiroati volume book. The instructor must undertake Qiroati education and training so as to obtain an official diploma with which to teach the Qiroati method. The purpose of this study was to analyze and describe the application of the Qiroati method in learning Al-Quran at SDIT Insantama Leuwiliang.